The Impact of Product Development Challenges on Innovation Management of Charcoal Briquettes in Medan (Case Study: Rumah Briket Medan Amplas) - Ningrum, Utrie Sekar Ayu; Syahreza, Dina Sarah; Ovianti, Widya; Siburian, Kristina; Khairunnisa, Khairunnisa; Manurung, Karina (Economic: Journal Economic and Business, 2024)
The purpose of this research is to know and analyze the The Impact of Product Development Challenges on Innovation Management of Charcoal Briquettes at the Medan Amplas Briquette House. The research method used is a qualitative method with interviews and literature study as data collection techniques. Based on survey result releved that limited resources and technology, low knowledge and expertise, and limited market access are the main challenges. To address this issue, partnerships with research institutions, employee training, and digital marketing are recommended. Implementation of this strategy is expected to increase production efficiency, competitiveness and business desirability. This research provides guidance for other SMEs and encourages further research into sustainable product innovation.